2011
DOI: 10.1159/000329722
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Phosphatase Is Increased in both Brain and Plasma in Alzheimer’s Disease

Abstract: Background: Tissue non-specific alkaline phosphatase (TNAP) has been shown to promote the neurotoxicity of extracellular tau which contributes to the spread of pathology in Alzheimer’s disease (AD). Objective: To investigate changes in TNAP activity in the hippocampus in both sporadic and familial AD, and to examine whether changes in neuronal TNAP are reflected systemically by looking at changes in plasma TNAP activity in AD. Methods: We measured the activity of TNAP in the hippocampus in sporadic AD, familia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 54 publications
3
61
0
Order By: Relevance
“…In addition, this region also harbors GWAS associations with traits ranging from TNFα response in patients with rheumatoid arthritis (45) to hematologic traits (46). While the physiological function of ALPLs are unknown, and no direct correlations have been made between ALPL variants and cognitive function, tissue non-specific ALPL is increased in Alzheimer’s disease patients (47). Furthermore, Alzheimer’s disease patients have an increased risk of suffering a stroke (48).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this region also harbors GWAS associations with traits ranging from TNFα response in patients with rheumatoid arthritis (45) to hematologic traits (46). While the physiological function of ALPLs are unknown, and no direct correlations have been made between ALPL variants and cognitive function, tissue non-specific ALPL is increased in Alzheimer’s disease patients (47). Furthermore, Alzheimer’s disease patients have an increased risk of suffering a stroke (48).…”
Section: Discussionmentioning
confidence: 99%
“…ALP is a sensitive marker of liver function and levels are often elevated in obese individuals (Golik et al, 1991). This is concerning, as higher ALP concentrations are seen in Alzheimer's disease patients and correlated with the neurotoxic effects of tau protein (Vardy et al, 2012; Diaz-Hernandez et al, 2010). Fortunately, ALP concentrations have been shown to improve following bariatric surgery (Toolabi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although ecto-nucleotidases, and TNAP in particular, have been studied in Alzheimer disease [31,49], no data were available on human ecto-nucleotidase expression in mental disorders such as SZ. By analyzing brain membranes, we have shown that NTPDase activity (both ATPase and ADPase) is significantly reduced in the putamen of SZ patients when compared with control samples.…”
Section: Discussionmentioning
confidence: 99%